Effect of Different Growing Media on the Growth of Cellulolytic Bacteria from Oryctes rhinoceros Larva - Sitepu, Andreas; Marheni, Marheni; Sitepu, Suzanna Fitriany (Universitas Gadjah Mada, 2025)
Oryctes rhinoceros larvae are one of the sources of cellulose and hemicellulose degrading bacteria. Nutrition and energy sources together, with environmental factors have significant impacts on cellulolytic bacteria growth. Carboxymethyl Cellulose (CMC) media is a media often used to obtain cellulosic bacteria, while Nutrient Agar (NA) media is used for bacteria propagation. The use of NA for bacterial growth media is expensive. For the growth of O. rhinoceros symbiont cellulolytic bacteria, it is necessary to use alternative media that are cheap, easily available and contain sufficient nutrients to sustain bacterial growth. Soybeans, mackerel tuna, and jackfruit seeds contain high levels of protein and carbohydrate, which can be used as a nitrogen and carbon source for cellulolytic bacteria growth are easily available and cheap. This makes them excellent alternative for growth media materials. The aim of this research was to determine growth of symbiotic cellulolytic bacteria from O. rhinoceroson different alternative growth media. The research was conducted from January to May 2024 at the Plant Disease Laboratory, Faculty of Agriculture and Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, University of Sumatera Utara. The experimental method used a factorial Completely Randomized Design (CRD) with 2 factors and 3 replications for each treatment combinations. The results showed that alternative growth media were suitable to sustain cellulolytic bacteria. The best treatment was mackerel tuna flour media with an average number of colonies of 100.5×106CFU/mL.